Relapses of pain syndrome in patients with polymyalgia rheumatica during reduction of glucocorticoid therapy - N. V. Bunchuk (Klinicist)
An analysis of causes leading to pain recurrence in patients with polymyalgia rheumatica (PR) after tapering down the dose of glucocorticosteroids (GCS) is presented. True exacerbations resulting from the main disease recurrence and pseudo-exacerbations when the resumption of pain syndrome is not due inflammation but because of other causes – steroid myopathy or chronic adrenal insufficiency (AI) are identified. The experience of using tocilizumab, an inhibitor of interleukin-6 receptors, as steroid-sparing agent in patients with PR is considered. The factors contributing to pain syndrome development, which can mimic exacerbations of PR (associated myofascial pain, vitamin D deficiency, etc.) are indicated. The methodology for AI diagnosis in patients receiving GCS therapy is discussed in detail. Recommendations for the rational AI therapy including acute cases are given.